Comparison of Efficacy of Foam Sclerotherapy with and without Ultrasound Guided for the Treatment of Varicose Veins - Umar, Muhammad; Pervaiz Butt, LT Col Hafiz khalid; Saleem, Irfan; Sikandar, Aneeza; Farooqi, Birya; Shahzad, Saba (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To compare the efficacy of foam sclerotherapy with and without ultrasound guided (Palpatory method) in the treatment of great saphenous and tributary varicose vein. Place & Duration of Study: This Randomized controlled trial was conducted at Vascular surgery department, CMH Lahore during June to December 2023. Methodology: Patients were enrolled and randomly divided in two equal groups. In group A, foam sclerotherapy was perfumed under ultrasound guidance. In group B, foam sclerotherapy was perfumed without ultrasound guidance. Duration of procedure was noted. Total number of sessions to achieve complete thrombosis of great saphenous vein, number of pricks required to achieve a successful cannulation, Post-procedure bruises, deep venous thrombosis and extravasation of foam were examined. All the data was recorded in proforma. Data was entered into SPSS version 25. Results: The mean age of patients was 42.72 ± 14.01 years in group I (ultrasound guided procedure) and 43.69 ± 13.19 years in group II (conventional treatment for varicose veins). In group I, all were males (100%) while in group II, there were 31 (96.9%) males and 1 (3.1%) was female. In group I, the mean time for procedure was 6.47 ± 1.22 minutes and in group II, mean time for procedure was 7.59 ± 1.36 minutes (p<0.05). Conclusion: Ultrasound guided method is more appropriate and as better outcomes than conventional treatment. Now in future, we will use ultrasound guided treatment of varicose veins.